Dexamethasone implant for non-infectious uveitis: is it cost-effective?. Issue 11 (11th February 2019) - Squires, Hazel; Bermejo, Iñigo; Poku, Edith N; Cooper, Katy; Stevens, John; Hamilton, Jean; Wong, Ruth; Denniston, Alastair K; Pearce, Ian; Quhill, Fahd Mohammed
Abstract : Background: Uveitis is inflammation inside the eye. The objective of this study is to assess the cost-effectiveness of a dexamethasone implant plus current practice (immunosuppressants and systemic corticosteroids) compared with current practice alone, in patients with non-infectious intermediate, posterior or pan-uveitis and to identify areas for future research. Methods: A Markov model was built to estimate the costs and benefits of dexamethasone. Systematic reviews were performed to identify available relevant evidence. Quality of life data from the key randomised-controlled trial (HURON) was used to estimate the interventions' effectiveness compared with the trial's comparator arm (placebo plus limited current practice (LCP)). The analysis took a National Health Service and Personal Social Services perspective. Costs were calculated based on standard UK sources. Results: The incremental cost-effectiveness ratio (ICER) of one dexamethasone implant compared with LCP is estimated as £19 509 per quality-adjusted life year (QALY) gained. The factors with the largest impact on the results were rate of blindness and relative proportion of blindness cases avoided by dexamethasone. Using plausible alternative assumptions, dexamethasone could be cost saving or it may be associated with an ICER of £56 329 per QALY gained compared with LCP. Conclusions: Dexamethasone is estimated to be cost-effective using generally accepted UK thresholds. However, there is substantial uncertainty around these results due to scarcity of evidence. Future research on the following would help provide more reliable estimates: effectiveness of dexamethasone versus current practice (instead of LCP), with subgroup analyses for unilateral and bilateral uveitis, incidence of long-term blindness and effectiveness of dexamethasone in avoiding blindness.